1997
DOI: 10.1111/j.1528-1157.1997.tb04537.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Health of Women with Epilepsy: Science and Ethics in New Drug Development

Abstract: Summary:Issues of unique concern to women with epilepsy largely arise from gender-based physiological differences. Female sex steroid hormones may alter the expression of epilepsy and the efficacy of antiepileptic drugs (AEDs). Seizures and AEDs in turn affect the hypothalamic-pituitary axis and can adversely impact reproductive function and bone health. Maternal seizures and exposure to AEDs may compromise fetal development. At this time, women with epilepsy and their medical caretakers do not have access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Concerns and psychopathology reflect social as well as biological differences. Female patients in general exhibit more illness behavior than males [44], whereas issues unique to women with epilepsy largely arise from gender-based physiological differences affecting the hypothalamicpituitary axis, which can adversely impact endogenous reproductive hormones as well as affective health [45,46].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Concerns and psychopathology reflect social as well as biological differences. Female patients in general exhibit more illness behavior than males [44], whereas issues unique to women with epilepsy largely arise from gender-based physiological differences affecting the hypothalamicpituitary axis, which can adversely impact endogenous reproductive hormones as well as affective health [45,46].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Most WWE appear to have normal sex lives, although approximately 33% to 50% of them may experience some degree of sexual dysfunction. 2,24,40,41 Greater levels of anxiety and apathy related to sexual performance as well as reduced vaginal lubrication and genital blood flow and increased dyspareunia and anorgasmia during intercourse have been reported. 3,40 A multifactorial cause appears operational.…”
Section: Sexualitymentioning
confidence: 99%
“…[3][4][5][6]13,31,36,40 Seizures arising from limbic structures disrupt function in the neighboring hypothalamus and medial frontal lobe, which are important in regulating expression of libido and arousal. 40,41 Also, seizures electrically alter hormonal function 14 via pituitary secretion, creating sexual dysfunction. 40 It has been reported that AEDs can interfere with circulating sex steroid concentrations 2,3,6 and directly influence mood and behavior, thereby affecting sexual desire.…”
Section: Sexualitymentioning
confidence: 99%
“…In particular, this condition is associated with VPA treatment, suggesting inibition of steroid hormones by this AED [30]. Other studies report polycystic ovaries associated to other AEDs [33]. This entity includes also hirsutism, acne, obesity, elevated androgens, an elevated LH: FSH ratio, chronic anovolution, and insulin resistance [34], and can be associated, among other disturbances, with infertility, an elevated risk for cardiovascular disease and dyslipidemia, and endometrial and breast cancer [35].…”
Section: Effects Of Epilepsy On Special Women Eventsmentioning
confidence: 95%